Molecular basis for diversification of yeast prion strain conformation - Ohhashi, Yumiko (Proc Natl Acad Sci U S A, 2018)
Self-propagating β-sheet–rich fibrillar protein aggregates, amyloid fibers, are often associated with cellular dysfunction and disease. Distinct amyloid conformations dictate different physiological consequences, such as cellular toxicity. However, the origin of the diversity of amyloid conformation remains unknown. Here, we suggest that altered conformational equilibrium in natively disordered monomeric proteins leads to the adaptation of alternate amyloid conformations that have different phenotypic effects. We performed a comprehensive high-resolution structural analysis of Sup35NM, an N-terminal fragment of the Sup35 yeast prion protein, and found that monomeric Sup35NM harbored latent local compact structures despite its overall disordered conformation. When the hidden local microstructures were relaxed by genetic mutations or solvent conditions, Sup35NM adopted a strikingly different amyloid conformation, which redirected chaperone-mediated fiber fragmentation and modulated prion strain phenotypes. Thus, dynamic conformational fluctuations in natively disordered monomeric proteins represent a posttranslational mechanism for diversification of aggregate structures and cellular phenotypes.